2019
DOI: 10.1111/wej.12489
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' resilience behaviour in the face of water scarcity in the eastern part of Lake Urmia, Iran: an environmental psychological analysis

Abstract: This study aimed to perform an environmental-psychological analysis of farmers' resilience behaviours towards water scarcity crisis. The study was descriptivecorrelational and causal-relational and was carried out as a survey. The statistical population was composed of farmers in Aji-Chay Basin in the eastern part of Lake Urmia (N = 417000), of whom 384 people were selected using stratified random sampling method. The instrument was a questionnaire whose validity was confirmed by a panel of experts. Its reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 39 publications
(37 reference statements)
2
11
0
Order By: Relevance
“…In this study, path analysis was conducted using the multiple linear regression method. Numerous studies have established and tested such a causal chain for the purpose of behavioral evaluation (Ebrahimi Sarcheshmeh et al , 2018; Mohammadi‐Mehr et al , 2018; Raeisi et al , 2018; Boazar et al , 2019; Shojaei‐Miandoragh et al , 2019; Valizadeh et al , 2019). Multiple regression analysis showed that the research causal model significantly explained the observed variance in farmers' WREB, level of motivation, time perspective, environmental attitudes, cultural attitudes and time norms.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, path analysis was conducted using the multiple linear regression method. Numerous studies have established and tested such a causal chain for the purpose of behavioral evaluation (Ebrahimi Sarcheshmeh et al , 2018; Mohammadi‐Mehr et al , 2018; Raeisi et al , 2018; Boazar et al , 2019; Shojaei‐Miandoragh et al , 2019; Valizadeh et al , 2019). Multiple regression analysis showed that the research causal model significantly explained the observed variance in farmers' WREB, level of motivation, time perspective, environmental attitudes, cultural attitudes and time norms.…”
Section: Resultsmentioning
confidence: 99%
“…An answer to this question may shed light on the question of whether or not the lake can be sustainably restored. In the Urmia lake basin, numerous studies have been conducted on the behavior of humans regarding water consumption (Anbari et al, 2021;Mahdavi, 2021;Pouladi et al, 2019Pouladi et al, , 2021Sadeghi et al, 2020;Shojaei-Miandoragh et al, 2020). The purpose of these studies was to identify human factors contributing to Lake Urmia's dryness and to suggest solutions to resolve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…If the current rate of water use is not diminished, economic development might be hampered, reducing food security while increasing poverty, hunger, conflicts, mass immigration, and the possibility of war [2][3][4][5]. Combined with predictions about population growth, urbanization, industrialization, and climate change, this situation could be much worse in the near future [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%